LISTENING LEARNING OF DRAMA EMPLOYING CONTEXTUAL APPROACH FOR STUDENTS OF VOCATIONAL HIGH SCHOOLS IN CENTRAL JAVA - Sumarni, Sumarni; Suwandi, Sarwiji; Waluyo, Herman; Andayani, Andayani (Universitas Pendidikan Indonesia, 2019)
In learning Indonesian language and literature needs to take into consideration the involvement of students in creative process. Students are capable of listening the literary works and appreciate them. The implementation of listening learning can be successful if it is employing a contextual approach. This study describes: (1) the needs of teachers and students in developing interactive media in listening learning of drama for students in Vocational High Schools; (2) the arrangement of interactive media prototype employing contextual approach in listening learning of drama for students in Vocational High Schools; (3) the effectiveness of interactive media employing contextual approach in listening learning of drama for students in Vocational High Schools; (4) the acceptance of interactive media employing contextual approach in listening learning of drama for students in Vocational High Schools based on stakeholders’ responses.The research employs Research and Development (RD) study that conducts some steps developed by Borg and Gall, as follows: 1) the exploratory study that includes literature review, field study and the initial phases in creating prototype design, 2) the development phase of new learning media, 3) the experiment phase that is to test the effectiveness of old media and new media in listening learning of drama, 4) the acceptance test of new learning media to public. The data was collected and tested its effectiveness with the T-Test statistical analysis.The results of this research show that; (1) teachers and students find difficulties to employ interactive media in listening learning of drama in accordance with the students’ basic competence and lesson plan, (2) the prototype of interactive learning media is developed, (3) the students’ learning outcome of listening learning of drama can be improved with the help of interactive media compared with the learning without it and this is proved by the results of limited field trial and field trial, (4) the interactive media can be accepted by public and has more advantages than the old media according to the result of acceptance test.